The Efforts of Islamic Religious Education Teachers to Increase the Student Learning Interest - Fajri, Habibi; Hernisawati, Hernisawati; Irhamuddin, Irhamuddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to determine how students' interest in learning Islamic religious education and the efforts of religious teachers in increasing students' interest in learning Islamic religious education as well as obstacles and support in increasing this interest. This research was conducted at SMA Ma'arif 01 Seputih Banyak. The type of research used in this research is descriptive qualitative. And the results obtained are the results of descriptive data, namely in the form of words, images not numbers. Sources and information are from religion teachers and students as well as parties involved in this research when needed. The results of this study are 1). Students' interest in learning Islamic religious education at SMA Ma'arif 01 Seputih Banyak is very good and also has high enthusiasm. 2). The efforts made by teachers in increasing student interest in Ma'arif 01 High School are: a) motivation, b). habituation of congregational prayer, c) explaining the purpose of the lesson, d. Practice, e. The class is not empty, f. Giving students freedom, g. Giving students freedom. Giving students freedom, g. Teacher's ability. The contribution of this research is to provide insights for teachers and schools in designing more effective strategies to increase student interest in learning Islamic religious education, as well as identifying factors that can support or hinder the learning process. Thus, it is hoped that this research can be a reference in developing better curriculum and teaching methods in the future.